Implementasi Algoritma AES pada Autentikasi Login Sistem Informasi - Fadlullah Fadlullah; Muhlis Tahir; Briliant Pijar Bintari; Mia Liana Dewi; Muhammad Fahri Ilmy; Syafi’ Syafi’; Rama Ardiansyah (Jurnal Bintang Pendidikan Indonesia, 2023)
The more rapid development of information technology, this has an impact and can cause changes in people's thinking patterns in communicating. In the past, the way people used to communicate remotely was still manual, namely by using letters. The lack of efficiency in sending letters encourages people's mindsets to create innovations that facilitate long-distance communication, namely via SMS, email, WhatsApp and the internet. One of the impacts of the development of message delivery technology is the tapping of data which makes the user feel insecure. One way to secure data breaches is by securing the sender's and recipient's email passwords using AES (Advanced Encryption Standard) cryptography. We conclude that the AES algorithm can be applied to encrypt passwords, so that passwords cannot be easily read by other users. In addition, the password will not be easily cracked.